Adding value to performance measurement by using system dynamics and multicriteria analysis - Santos, Sérgio Pereira dos (2014)
The design, implementation and use of adequate performance measurement and management frameworks can play an important role if organisations are to succeed in an increasingly complex, interdependent and changing world. Yet, despite widespread recognition of the importance of performance assessment, there are some issues that require further study if measurement systems are to be effective in the process of management through monitoring and decision making. This article proposes and seeks to illustrate that the use of system dynamics and multicriteria decision analysis, as part of a broader framework for performance measurement, can address some of the issues identified. The use of these approaches, independently and in an integrated manner, provides a means of exploring the dynamic complexity of organisations, making explicit trade-offs between performance measures, and assessing the impacts of initiatives to improve performance, thereby enhancing understanding and ultimately contributing to the improvement of organisational performance.